2015
DOI: 10.1021/jacs.5b01404
|View full text |Cite
|
Sign up to set email alerts
|

Microsecond Deprotonation of Aspartic Acid and Response of the α/β Subdomain Precede C-Terminal Signaling in the Blue Light Sensor Plant Cryptochrome

Abstract: Plant cryptochromes are photosensory receptors that regulate various central aspects of plant growth and development. These receptors consist of a photolyase homology region (PHR) carrying the oxidized flavin adenine dinucleotide (FAD) cofactor, and a cryptochrome C-terminal extension (CCT), which is essential for signaling. Absorption of blue/UVA light leads to formation of the FAD neutral radical as the likely signaling state, and ultimately activates the CCT. Little is known about the signal transfer from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
82
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(103 citation statements)
references
References 59 publications
17
82
0
4
Order By: Relevance
“…B, double difference spectrum of the 1 s spectrum minus the steady state spectrum was calculated. The comparison to reference spectra of TyrO ⅐ in water (red) (29) and at 140 K (blue) (30) reveals a red shift. A complete match is obtained by shifting the reference spectrum by 9 nm (inset).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…B, double difference spectrum of the 1 s spectrum minus the steady state spectrum was calculated. The comparison to reference spectra of TyrO ⅐ in water (red) (29) and at 140 K (blue) (30) reveals a red shift. A complete match is obtained by shifting the reference spectrum by 9 nm (inset).…”
Section: Resultsmentioning
confidence: 99%
“…2B). The comparison to reference spectra (29,30) revealed that such a band is characteristic for TyrO ⅐ . In contrast to the reference spectra obtained in water, TyrO ⅐ in aCRY is red-shifted by the protein environment by 9 nm (inset, Fig.…”
Section: Long-lived Tyrosyl Radical In the Animal-like Cryptochromementioning
confidence: 90%
See 2 more Smart Citations
“…It has been previously shown that conformational change involving the cry1 C-terminal domain occurs on a millisecond time scale, 33 which is too slow for triggering by direct electron and/or proton transfer events. More recent data suggests conformational change may be initiated already within the N-terminal domain at much more rapid time scales, 34 consistent with triggers such as deprotonation of D396, an aspartic acid residue in proximity to the flavin.…”
Section: The C-terminal Domain Of Cryptochrome Is Implicated In Strucmentioning
confidence: 54%